2011
DOI: 10.1093/annonc/mdq590
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant trastuzumab with thoracic radiotherapy: a morphological and functional study

Abstract: T and high-dose RT may lead to vascular damage that seems at least additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Bese et al (20) reported that concomitant use of T with RT (12 Gy) or subsequent use did not increase pulmonary fibrosis in rats. In another animal study, it was found that concomitant use of T with high-dose RT (15 Gy) resulted in might lead to vascular damage that seemed at least additive damage on thoracic aorta (21). In both studies, T was administered in 6 mg/kg dose, in consistent with our study.…”
Section: Discussionsupporting
confidence: 86%
“…Bese et al (20) reported that concomitant use of T with RT (12 Gy) or subsequent use did not increase pulmonary fibrosis in rats. In another animal study, it was found that concomitant use of T with high-dose RT (15 Gy) resulted in might lead to vascular damage that seemed at least additive damage on thoracic aorta (21). In both studies, T was administered in 6 mg/kg dose, in consistent with our study.…”
Section: Discussionsupporting
confidence: 86%
“…9 The 8 Gy dose of RT was not enough to cause significant changes both from functional and morphological aspects. On the other hand 15 Gy RT led significant changes.…”
Section: Discussionmentioning
confidence: 97%
“…The senior author worked on experimental composite allotransplantation and permanent immunotolerance using different therapeutic methods. 3 The aim of our experimental studies is to achieve permanent immune tolerance without the use of immunosuppressive drugs and develop novel clinical composite tissue allotransplantations in the future. 4,5 Nerve allotransplantations in replanted arms have been performed by the authors on 2 children, the younger of whom had total motor and sensorial recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the promising results of an experimental study performed by our radiation oncology team, which points to the advantage of preoperative irradiation to reduce the antigenic load of the transplanted extremities, 3 we irradiated the extremities preoperatively.…”
Section: Irradiation Of the Procured Extremitiesmentioning
confidence: 99%